Sperimentazione di rilievo UAV a supporto della pianificazione forestale - Prandi, Federico; De Amicis, Raffaele; Magliocchetti, Daniele (GEOmedia, 2015)
The project SLOPE will integrate information from, UAV and on-field surveying systems, to support macro and local analysis to characterize the forest resources. Spatial information will integrate data in a model for optimization of logistics during forest operations.